Fala Preta: Mulheres que constroem o Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This project documents the stories of Black women from Amapá through a documentary web series. It uses in-depth interviews and documentary journalism to narrate the experiences of Black women who help shape Amapá through individual struggles that become collective in relation to their land and their people. The web series aims to contribute to the collective memory of a people and to foster reflections on the role Black women occupy in society. As an academic work, it reinforces the role of journalism in valuing these narratives and in building a more just society.
Keywords: Mulheres Negras - Brasil; Jornalismo Documental; Memórias - Amapá; CNPQ::CIENCIAS SOCIAIS APLICACAS::COMUNICACAO::JORNALISMO E EDITORACAO